New enzymatically polymerized copolymers from 4-tert-butylphenol and 4-ferrocenylphenol and their modification and inclusion complexes with β-cyclodextrin - Mondrzyk, Adam; Mondrzik, Beate; Gingter, Sabrina; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2012)
The enzymatically catalyzed synthesis of a copolymer of 4-tert-butylphenol and 4-ferrocenylphenol by horse radish peroxidase (HRP) in the presence of H2O2 in a 1,4-dioxane/water system is described. Furthermore, polymer-analogous alkylation of the free hydroxy groups and subsequent click reaction with mono-6-azido-6-desoxy-β-cyclodextrin (N3-β-CD) was carried out. The formation of inter- and intramolecular inclusion complexes was investigated by DLS measurement.
Keywords: copolymer; ß-cyclodextrin; enzymatic polymerization; 4-ferrocenylphenol; polyphenol; 4-tert-butylphenol; horseradish peroxidase; HRP oxidative coupling; inclusion complexes; polymer-analogous modification